Effects of MTHFR C677T Gene Polymorphism on Migraine Together with Biochemical and Clinical Parameters in Turkish Population - Nisari, Mustafa; Baydemir, Recep (Progress in Nutrition, 2020)
To detect the relation between methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphism and both of clinical and biochemical parameters. One hundred sixty migraine patients and one hundred twenty control group were included in the current study. Pain intensity of individuals were measured, biochemical, clinical parameters and MTHFR C677T single nucleotide polymorphism were detected. Statistically higher occurrence MTHFR C677T genotype was detected in migraine group than control group. A statistically significant association between family history of migraine and MTHFR C677T genotypes was detected. Also, statistically higher BMI, homocysteine and the total cholesterol levels were detected in MO and MA groups than control groups. When we take into consideration of the clinical parameters, only statistically significant difference was detected between MA and MO for attack frequency (attack/ monthly). The triglyceride and homocysteine levels were significantly higher in males than females but HDL levels and folate were significantly higher in females than males. The frequency of CT genotype was significantly higher in cases with compression and allodynia than others in MA groups and cases with fatigue in both MA and MO subgroups. Also, cases without systemic complaints had significantly higher T allele frequency than cases with systemic complaints in the MA subgroup. Because the labor losses of patients with migraine may cause important economic losses, performed studies for the fully understanding of the disease including genetic and environmental factors are important for the prevention of negativity caused by the disease.